LACONISS: A planning support system for land consolidation - Demetriou, Demetris; Stillwell, John; See, Linda (My University, 2013)
Land consolidation is considered as the most effective land management planning approach for solving the land fragmentation problem in rural areas and more broadly to assist the implementation of regional and urban planning. This chapter focuses on a planning support system for land consolidation in rural areas called Land CONsolidation Integrated Support System for planning and decision making (LACONISS) that integrates GIS, artificial intelligence techniques and multi-criteria decision methods. The system involves four modules: the Land Fragmentation System (LandFragmentS) module measures existing land fragmentation in an agricultural context; the Land Spatial Consolidation Expert System (LandSpaCES) Design module produces alternative land redistribution plans; the LandSpaCES Evaluation module assesses these plans based on a set of criteria; and the Land Parcelling System (LandParcelS) module produces the final land partitioning plan. The final output is the land reallocation plan. The whole system has been applied to a case study area in Cyprus and this reveals that land fragmentation can be reliably measured, that alternative land reallocation plans can be produced that can successfully emulate planners’ reasoning, that the most beneficial plan for various combinations of criteria and weights can be identified and that the subdivision process can be automated satisfactorily although further improvements are needed. The contribution of LACONISS is relevant to both rural and urban sustainable development since it supports and automates the land reallocation (or land readjustment) process which is the principal component of any land consolidation project whether rural or urban. Eventually, LACONISS may constitute the foundations for developing a generic system that could be applied in any country that implements land consolidation projects.
Keywords: Expert systems; Planning; Principal component analysis; Rural areas